Soviet repressions in Estonia: remembrance and commemoration in XXI century. - Anepaio, Terje (Genocidas ir rezistencija, 2008)
In the 1990s, Estonian society was particularly strongly and unequivocally future-oriented, and memories of the repressions were fading at an astonishing rate. By the end of the 1990s, the Estonian elite had already realised that ‘something had to be done’ to strengthen the continuity and transmission of the nation’s past (the experience of repression) to society, as well as the dialogue between different generations. The commemoration and perpetuation of events of national importance (e.g. war) occurs on three levels: national, civil society organisations and personal (family and kinship settings, face-to-face encounters). At the beginning of the 21st century, Estonian society has matured with regard to the remembrance and commemoration of repression. This is confirmed by the following examples: first, the extensive campaign of actualization of the past, which aimed at spreading the memory of the past between generations and which emphasized the symbolic value of the repressed for society; second, the increased efforts of the repressed to make themselves heard and to contribute to the preservation of the memory of the repressions, as shown by the activities of the Union of the Broken Cornflower; and third, the hidden aspect of the memory of repression, namely, the wilful appearance of the memories of the pain and the atrocities, which have been suppressed until today, in the public domain through the mediation of the second generation.